The effects of exercise training on insulin resistance in children and adolescents with overweight or obesity: a systematic review and meta-analysis - Kazeminasab, Fatemeh; Sharafifard, Fatemeh; Miraghajani, Maryam; Behzadnejad, Nasim; Rosenkranz, Sara K. (Frontiers in Endocrinology, 2023)
Aim: The aim of present meta-analysis was to determine the effects of exercise training (Exe) on insulin resistance (IR) and body weight in children and adolescents with overweight or obesity. Methods: PubMed, Web of Science, and Scopus were searched for original articles, published through October 2022 that included exercise versus control interventions on fasting glucose, insulin, HOMA-IR, and body weight outcomes in children and adolescents with overweight or obesity. Standardized mean differences (SMD) for fasting insulin, and weighted mean differences (WMD) for fasting glucose, HOMA-IR, body weight (BW), and 95% confidence intervals were determined using random effects models. Results: Thirty-five studies comprising 1,550 children and adolescents with overweight and obesity were included in the present meta-analysis. Exercise training reduced fasting glucose (WMD=-2.52 mg/dL, p=0.001), fasting insulin (SMD=-0.77, p=0.001), HOMA-IR (WMD=-0.82, p=0.001), and BW (WMD=-1.51 kg, p=0.001), as compared to a control. Subgroup analyses showed that biological sex, intervention duration, type of exercise training, BMI percentile, and health status (with or without diagnosed condition), were sources of heterogeneity. Conclusion: Exercise training is effective for lowering fasting glucose, fasting insulin, HOMA-IR, and BW in children and adolescents with overweight or obesity, and could provide an important strategy for controlling IR and related factors. With clear evidence for the effectiveness of exercise interventions in this vulnerable population, it is important to determine effective approaches for increasing exercise training in children and adolescents with overweight or obesity.